Understanding how communities respond to COVID-19: experiences from the Orthodox Jewish communities of Antwerp city - Jef Vanhamel; Marie Meudec; Ella Van Landeghem; Maya Ronse; Charlotte Gryseels; Thijs Reyniers; Anke Rotsaert; Charles Ddungu; Lazare Manirankunda; Deogratias Katsuva; Koen Peeters Grietens; Christiana Nöstlinger (BMC, 2021)
Abstract Background The importance of community involvement in the response against disease outbreaks has been well established. However, we lack insights into local communities' experiences in coping with the current COVID-19 pandemic. This study explored both the impact of, and response to, COVID-19 within the Orthodox Jewish communities of Antwerp (Belgium) during the first lockdown period (March 2020 - May 2020). Methods We conducted an explorative qualitative study using a participatory approach. First, we performed a community mapping to identify relevant stakeholders. Through the active involvement of a community advisory board and based on qualitative interviews with key-informants and community members, we elicited lived experiences, attitudes, and perceptions towards COVID-19. Interviews were conducted both face-to-face and using online web conferencing technology. Data were analyzed inductively according to the principles of thematic analysis. Results Government-issued outbreak control measures presented context-specific challenges to the Orthodox Jewish communities in Antwerp. They related mainly to the remote organization of religious life, and practicing physical distancing in socially and culturally strongly connected communities. Existing community resources were rapidly mobilized to adapt to the outbreak and to self-organize response initiatives within communities. The active involvement of community and religious leaders in risk communication proved to be of great importance to facilitate the coverage and uptake of pandemic control measures while protecting essential community values and traditions. Creating bottom-up and community-adapted communication strategies, including addressing language barriers and involving Rabbis in the dissemination of prevention messages, fostered a feeling of trust in government's response measures. However, unmet information and prevention needs were also identified, such as the need for inclusive communication by public authorities and the need to mitigate the negative effects of stigmatization. Conclusion The experiences of Orthodox Jewish communities in Antwerp demonstrate a valuable example of a feasible community-centered approach to health emergencies. Increasing the engagement of communities in local decision-making and governance structures remains a key strategy to respond to unmet information and prevention needs.